The Implementation of Teaching Assistant Through MBKM Program: Pre-Service Teachers’ and Host Teachers' Perceptions - Miftahul Fadhila, Rendra; Abdul Karim, Sayit; Winarna; Matas, Gordan (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Pre-service teachers are urged to broaden their perspectives through interactions with school residents, students, and direct exposure to real-world situations. This study aims to explore the perceptions of pre-service teachers at the Universitas Teknologi Yogyakarta (UTY), and the host teachers from SMKN 1 Godean regarding teaching assistants through the Merdeka Belajar Kampus Merdeka (MBKM) program, and further identify challenges encountered during its implementation. Qualitative descriptive research was utilized, and the data were obtained through open-ended questions, and a semi-structured interview. 18 respondents participated in the present study, including 5 students from ELESP, 5 students of Technology and Information Education, 5 students from guidance counseling, and 3 host teachers from SMKN 1 Godean. The data analysis in this research is based on Miles & Huberman's interactive model theory (1994). The researchers discovered that pre-service teachers from UTY and host teachers from SMKN 1 Godean have similar perceptions of teaching assistants in the MBKM program. Teaching assistants are opportunities for pre-service teachers to get teaching and administrative experience out of campus. Their perceptions of these programs include gaining new knowledge, and experience, being ready for teaching, and using teaching methods appropriately. Pre-service teachers countered challenges regarding pedagogical issues, subject-matter knowledge, and communication skills